THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND FAMILY ENVIRONMENT ON ENTREPRENEURIAL INTERESTS THROUGH SELF-EFFICACY - Riva Karomatul Azizah; Triesninda Pahlevi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to measure the effect of entrepreneurship education on entrepreneurial interest, the family environment on entrepreneurial interest, entrepreneurship education on self-efficacy, the family environment on self-efficacy, self-efficacy on entrepreneurial interest, and entrepreneurship education on entrepreneurial interest mediated by self-efficacy, as well as the family environment on the entrepreneurial interest mediated by self-efficacy. This research was conducted on students of Office Administration Education Study Program at Universitas Negeri Surabaya registered in 2018 which consisted of 62 students. All populations were used as samples in this research. This research technique was quantitative research with causal associative types and primary data types. Data were collected by using Self-Administered Surveys. Then, the data were analyzed by using path analysis. The research output concluded that entrepreneurship education did not have a positive impact on entrepreneurial interest (P Value = 0.789), the family environment had a positive and significant impact on entrepreneurial interest (P Value = 0.030), self-efficacy had a positive impact on entrepreneurial interest (P Value = 0.000 ), entrepreneurship education had a positive and significant impact on self-efficacy (P Value = 0.000), family environment had a positive and significant impact on self-efficacy (P Value = 0.044), entrepreneurship education had a positive and significant impact on entrepreneurial interest mediated by self-efficacy (P Value = 0.000), family environment did not have a positive and significant impact on the entrepreneurial interest mediated by self-efficacy(P Value = 0.107).